The intellectual foundations of modern Ukraine : the nineteenth century - Zayarnyuk, Andriy, 1975-; Sereda, Ostap (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This is the first synthetic book-length study in English of the Ukrainian nation-building during the "long" nineteenth century. The Intellectual Foundations of Modern Ukraine is the ideal resource for upper-level undergraduates, postgraduates, and scholars interested in cultural anthropology, political science, political philosophy, and the history of modern Ukraine"--
The Land -- Mapping Peoples -- A People of One's Own -- Romantics and Universities -- Ukraine : Polish, Russian, and Slavic -- Ukraine as the People -- Winds of Change -- Across the Imperial Border -- Ukraine as Progress : Mykhailo Drahomanov -- "Apolitical" Ethnography -- Modernities and Modernisms -- Ethnographies, Anxieties, and Identities -- The Nation-State and Alternatives -- Visibility : At Home and Abroad.
Keywords: Nationalism -- Ukraine -- History -- 19th century; Intellectuals -- Ukraine -- History -- 19th century; Ukraine -- Politics and government -- 19th century; Ukraine -- History -- Autonomy and independence movements; Ukraine -- Relations -- Russia; Russia -- Relations -- Ukraine; Ukraine -- History -- 1775-1917.; HISTORY / Europe / Eastern; HISTORY / Modern / 19th Century; HISTORY / Europe / Russia & the Former Soviet Union